2015
DOI: 10.1039/c4nj02147a
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide inhibition, antioxidant, and antitumour activities of novel copper(ii) bis-benzimidazole diamide nanocoordination complexes

Abstract: Antitumor effect illustrated by changes in body weight. In control mice, body weight increased to 11.5 g but when treated withC3, body weight difference as compared to the control decreased by 4.7 g and decreased to 2.2 g and 0.6 g withC1andC2, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Metal ions are known to combine with many drugs and/or organic ligands to form complexes with enhanced ligand bioactivity. This made the metal complexes to be widely used in medicinal, pharmaceutical, agricultural, and chemical industries. ,, Recent reports indicate that due attention is being given to the chemistry of metal–organic compounds and their clinical applications for the treatment of various disorders, including both communicable and non-communicable diseases. Accordingly, researchers’ interest has shifted toward the synthesis of metal complexes that have biological activities, such as antioxidant and antimicrobial activities. In the past few decades, studies have revealed that complexes of metalssuch as copper, chromium, cobalt, manganese, vanadium, and zinchave promising antimicrobial, anti-oxidant, anti-tumor, and antidiabetic properties. ,, The issue of metal-based therapy has witnessed increasing focus with respect to efficient strategies in the design of repository, slow-release, or long-acting drugs . In this regard, heterocyclic ligands containing imine are important classes of biologically active molecules that have attracted attention of bioinorganic, pharmaceutical, and medicinal chemists due to their familiar coordination behavior and wide range of pharmacological properties. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Metal ions are known to combine with many drugs and/or organic ligands to form complexes with enhanced ligand bioactivity. This made the metal complexes to be widely used in medicinal, pharmaceutical, agricultural, and chemical industries. ,, Recent reports indicate that due attention is being given to the chemistry of metal–organic compounds and their clinical applications for the treatment of various disorders, including both communicable and non-communicable diseases. Accordingly, researchers’ interest has shifted toward the synthesis of metal complexes that have biological activities, such as antioxidant and antimicrobial activities. In the past few decades, studies have revealed that complexes of metalssuch as copper, chromium, cobalt, manganese, vanadium, and zinchave promising antimicrobial, anti-oxidant, anti-tumor, and antidiabetic properties. ,, The issue of metal-based therapy has witnessed increasing focus with respect to efficient strategies in the design of repository, slow-release, or long-acting drugs . In this regard, heterocyclic ligands containing imine are important classes of biologically active molecules that have attracted attention of bioinorganic, pharmaceutical, and medicinal chemists due to their familiar coordination behavior and wide range of pharmacological properties. ,, …”
Section: Introductionmentioning
confidence: 99%
“…As a notable instance of second generation metal-based anticancer agents, Ru(II) metal complexes such as NAMI-A or KP1019 have reached clinical trial steps [159][160][161]. To date, other less explored transition metal ions such as gold, Rhodium, Iridium, iron, palladium, silver, antimony, bismuth, copper and tin have aroused increasing attention [157,[162][163][164]. Until very recently, Rh(III) and particularly Ir(III) complexes, were generally regarded as unsuitable candidates as anticancer agents owing to the typical kinetic inertness of their transition metal centres.…”
Section: V2 Introductionmentioning
confidence: 99%
“…As a notable instance of second generation metal-based anticancer agents, Ru(II) metal complexes such as (H 2 im)[Ru III Cl 4 (DMSO)(Him)] (Him = 1H-imidazole) (NAMI-A) or trans-[tetrachlorobis(1Hindazole)ruthenate(III)] (KP1019) have reached different phases of clinical trial [4][5][6]. To date, other less explored transition metal ions such as gold, rhodium, iridium, iron, osmium, palladium, silver, antimony, bismuth, copper and tin have aroused increasing attention [1,[7][8][9][10][11][12]. Until very recently, Rh(III) and particularly Ir(III) complexes were generally regarded as unsuitable candidates as anticancer agents owing to the typical kinetic inertness of their transition metal centres.…”
Section: Introductionmentioning
confidence: 99%